Measurement of the b-hadron production cross section using decays to D∗+μ−X final states in pp collisions at √s = 7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2012)
The b-hadron production cross section is measured with the ATLAS detector in pp collisions at √s = 7 TeV, using 3.3 pb−1 of integrated luminosity, collected during the 2010 LHC run. The b-hadrons are selected by partially reconstructing D∗+μ−X final states. Differential cross sections are measured as functions of the transverse momentum and pseudorapidity. The measured production cross section for a b-hadron with pT > 9 GeV and |η| < 2.5 is 32.7±0.8(stat.)+4.5 −6.8(syst.) μb, higher than the next-to-leading- order QCD predictions but consistent within the experimental and theoretical uncertainties.